Ad hoc properties and locations in Maltese - Gréte Dalmi (LingBaW)
This paper aims to show that the four-way BE-system of Maltese can best be accommodated in a theory of non-verbal predication that builds on alternative states, without making any reference to the Davidsonian spatio-temporal event variable. The existing theories of non-verbal predicates put the burden of explaining the difference between the ad hoc vs. habitual interpretations either solely on the non-verbal predicate, by postulating an event variable in their lexical layer (see Kratzer 1995; Adger and Ramchand 2003; Magri 2009; Roy 2013), or solely on the copular or non-copular primary predicate, which contains an aspectual operator or an incorporated abstract preposition, responsible for such interpretive differences (Schmitt 2005, Schmitt and Miller 2007, Gallego and Uriagereka 2009, 2011, Marín 2010, Camacho 2012).